2011
DOI: 10.1007/s10802-011-9569-4
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Equivalence Across Racial/Ethnic Groups of the Mood and Feelings Questionnaire for Childhood Depression

Abstract: As research continues to document differences in the prevalence of mental health problems such as depression across racial/ethnic groups, the issue of measurement equivalence becomes increasingly important to address. The Mood and Feelings Questionnaire (MFQ) is a widely used screening tool for child and adolescent depression. This study applied a differential item functioning (DIF) framework to data from a sample of 6th and 8th grade students in the Seattle Public School District (N=3,593) to investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 49 publications
4
30
0
Order By: Relevance
“…We attempted to minimize this limitation by examining our research question in a population that generalizes to other consequential settings where standardized parent-report measures may be frequently used (families seeking outpatient services). A next step in understanding the internal structure of the MFQ will be examining both the youth-and parent-report MFQ in community and clinical samples so that the internal structure supported in this sample can be better understood in light of prior evidence of unidimensionality of the youth-report version in community samples (e.g., Banh et al 2012). Discrepancies in the internal structure of youth depression measures between community and clinical samples are not unprecedented and indeed have been found in other commonly used measures of youth depressive symptoms (e.g., CDI; Myers and Winters 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We attempted to minimize this limitation by examining our research question in a population that generalizes to other consequential settings where standardized parent-report measures may be frequently used (families seeking outpatient services). A next step in understanding the internal structure of the MFQ will be examining both the youth-and parent-report MFQ in community and clinical samples so that the internal structure supported in this sample can be better understood in light of prior evidence of unidimensionality of the youth-report version in community samples (e.g., Banh et al 2012). Discrepancies in the internal structure of youth depression measures between community and clinical samples are not unprecedented and indeed have been found in other commonly used measures of youth depressive symptoms (e.g., CDI; Myers and Winters 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Though these face valid content areas have been used by other investigators (e.g., Diler et al 2007;Hammerton et al 2014), psychometric assessment of the measure's internal structure is limited. The full, 33-item English language version of the youth-report MFQ has only been subjected to factor analyses in one sample (Banh et al 2012) with no prior analyses of the full, 34-item parent-report version of the measure. In Banh's study (2012), the internal structure of the youth-report MFQ was examined in a community sample, with results suggesting a unidimensional structure.…”
mentioning
confidence: 99%
“…Scores range between 0 (lowest risk of depressive symptoms) and 26 (highest) and the variable was dichotomised with a total score of eight or more indicating clinically relevant depressive symptoms [26]. This instrument has been validated within a range of ethnic groups in a variety of contexts and across languages [27,28].…”
Section: Mental Health Outcomesmentioning
confidence: 99%
“…Given the accumulating evidence about the high prevalence and debilitating related to childhood depression, a better understanding of the etiology of depression in youth is needed [16,17] Several investigations have demonstrated a wide variation in the prevalence of depression in children and differences according to the criteria of diagnostic classification adopted, mainly due to the diverse mode of presentation of depression and the association of this disorder with other psychopathologies [18]. Prevalence estimates among different racial/ethnic groups vary widely too [19]: American Indian youths reported the highest prevalence of depressive symptoms (29%), followed by Hispanic (22%), non-Hispanic White (18%), Asian American (17%), and African American (15%) youths [19,20]. Thus, knowing the risk factors for depression during childhood is essential for a better understanding of the etiology of this disorder and for planning prevention strategies [18].…”
Section: Social and Environmental Factorsmentioning
confidence: 99%
“…The study of BanH et al, [19] have sought to analyze the ethnic influence in depression. Their findings suggested that the MFQ (Mood and Feelings Questionnaire) demonstrates sufficient measurement equivalence for 6 th or 8 th graders, males and females, youth with US-and non-US born parents.…”
Section: Comorbiditiesmentioning
confidence: 99%